The Oxford handbook of American political history - Baker, Paula; Critchlow, Donald T., 1948- (New York : Oxford University Press, 2020)
"American political history, like military history, has never lost a popular audience. If anything, the appetite for books dealing with the nation's founding, its presidents, and elections has grown in recent years. Written by historians, academics in other fields, independent writers, and journalists, some of these books have sold very well. A few jumped from the printed page to film and theater. Ron Chernow's biography of Alexander Hamilton inspired a hit Broadway musical. Though some films depicting presidents spun fanciful stories-at least one hopes no teachers had to correct student misconceptions about Abraham Lincoln dispatching vampires-others had a stronger commitment to the historical record. Since 2000, Lincoln, Franklin D. Roosevelt, John F. Kennedy, Lyndon Johnson, Richard Nixon, and George W. Bush have been the focus of films with various levels of attentiveness to historical scholarship and box-office appeal. Teachers could do worse than Charlie Wilson's War as a tool for illustrating how Congress works. Even the more obscure and distant historical figures have had their turn: James A. Garfield's truncated presidency is the subject of a popular book and documentary"--
Includes bibliographical references and index.
Keywords: United States -- Politics and government